A case study on gamified interventions for team cohesion in factory work - Vegt, Niko; Visch, Valentijn; Vermeeren, Arnold; Ridder, Huib (Human Technology, 2018)
In this article, we aim to provide insights into the design and implementation of game elements for teamwork on the work floor and to study their effect. Inventing games to break monotonous jobs is a long-standing practice, yet conscious implementation of motivational elements of games at work is a recent phenomenon. Generally, gamification is used to enhance individual performance; it may be effective in enhancing teamwork as well. We developed game elements aimed at team cohesion and examined the effect of two gamified interventions (team performance feedback and personal profiles) on team cohesion in a factory. Results suggest that the interventions mainly raised attention toward the aspects of the work that were explicitly addressed. Team performance feedback led to increased task commitment and perceived team performance, while personal profiles increased nonwork-related conversations among team members. We conclude with lessons learned regarding the development and study of gamified interventions for teams on the work floor.